Comparison of statistical and non-statistical classifiers for thumb motion classification - Havlík, Jan; Horčík, Zdeněk (Lékař a technika, 2008)
This paper deals with a comparison of statistical and non-statistical classifi ers for thumb motion classifi cation. Presented work is a part of research of relation between brain and muscle activity. Th e thumb motion is represented by trajectory coordinates of special mark placed on the thumb. Motions are classifi ed using k-Means classifi er (non-statistical classifi cation, no prior information is needed) and Bayes classifi er (statistical models of classes are needed, classifi er training is necessary). Th e effi ciency of classifi ers is evaluated using the standard HTK parameters. Real testing data includes more than 900 stationary states which are used for classifi er testing. Th e classifi cation results are compared for both methods.
Keywords: financování organizované; Statistics as Topic; Movement; muskuloskeletální a nervový systém - fyziologické jevy; palec ruky; statistika jako téma; pohyb; Time and Motion Studies; svalová kontrakce; studie pohybu a času; ruka; Bayesova věta; shluková analýza; lidé; Bayes Theorem; Thumb; mozek; Video Recording; Financing, Organized; Musculoskeletal and Neural Physiological Phenomena; Brain; audiovizuální záznam; Hand; Muscle Contraction; Cluster Analysis; elektroencefalografie; Electroencephalography; Humans